Interests and Learning Achievements of Health Students in the Early Semester - Miadi Miadi; Lembunai Tat Alberta (Humanistic Network for Science and Technology (HNST), 2018)
The relationship between student interest and learning achievement, until now has not been widely studied. This study aims to explain the relationship between interest and learning achievement of first semester students, Surabaya Ministry of Health Polytechnic, with a cross sectional design. The research subjects were 400 Semester I students of the Poltekkes Kemenkes Surabaya, 2016/2017 Academic Year, which were selected by simple random sampling technique. Data about student interest is obtained from the results of psychological tests at the time of the selection of new students, while data on student achievement is obtained from the Academic Information system. The collected data were analyzed using the Spearman correlation test. Students who have high interest tend to have a better semester achievement index. Keywords: Interest, Learning achievement